Endothelial KLF4 depletion drives age-related neurovascular dysfunction and neuropsychiatric impairment - Matasha Dhar; Edwin Vázquez-Rosa; Kalyani Chaubey; Emiko Miller; Sofia G. Corella; Suwarna Chakraborty; Sunil Jamuna Tripathi; Tapatee Das; Xudong Liao; Mohamed Alkassem Alosman; Hua Fang; Yeojung Koh; et al. (Proceedings of the National Academy of Sciences, 2026)
Deterioration of the blood–brain barrier (BBB), including impaired neurovascular uncoupling, contributes to cognitive decline in aging. The BBB is formed principally by brain microvascular endothelial cells (ECs), and ECs throughout the body are enriched for the transcription factor Krüppel-like factor 4 (KLF4). Because KLF4 levels in ECs decrease with age, we tested whether that decline contributes to aging-related BBB deterioration, neurovascular dysfunction, and cognitive impairment. Using EC-specific Klf4 knockout mice (EC-K4KO), we show that loss of EC KLF4 accelerates multiple age-related brain pathologies. Indeed, middle-aged EC-K4KO mice display pathological features that are not normally observed until advanced age, including marked BBB leakage, impaired neurovascular coupling, loss of microvessels, increased oxidative damage, neuroinflammation, neurodegeneration, anxiety-like behavior, and cognitive deficits. Single-cell RNA sequencing of brain vasculature reveals dysregulation of immune response and barrier-related genes in ECs lacking KLF4, indicating that KLF4 maintains brain endothelial homeostasis by constraining proinflammatory and senescence programs at the chromatin level. Together, these results identify loss of EC KLF4 as a key driver of neurovascular decline and age-associated cognitive dysfunction.